The Didactic Fabric of Folklore: A Narrative Analysis of Values in “Bandha Warisan” - Riandita, Riandita; Bindarti, Wiwiek Eko; Chaloemkiti, Miss Treesirin; Trairat, Jaraswat; Cruz, Shella Dela (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to systematically identify, describe, and categorize the moral education values ​​contained in the Javanese folktale anthology